Screw consent : a better politics of sexual justice - Fischel, Joseph J. (University of California Press, 2019)
"When we think of sex--good sex, bad sex, sexual assault, rape law, or university sexual misconduct policies--we so often turn to consent as both our moral and erotic savior. What counts as sexual consent? How can we make consent sexy? How do we teach consent to impressionable youth, potential predators, and victims alike? What if these are all the wrong questions? Screw Consent is a provocative take on consent and whether its place at the center of sexual politics and sex law is warranted. The book takes aim at sex imagined at the center of our moral universe: adult, coupled, consensual. By spotlighting sex on the periphery--bestial, necrophilic, kinky, cannibalistic--Screw Consent shows that sex on the margins confounds the ethical force of consent much further than we anticipate. Author Joseph J. Fischel fervently argues that the consent paradigm of sexual politics is profoundly flawed. In addition to the criticisms against consent leveled by feminist theorists of earlier generations, Fischel elevates three more: consent is insufficient, inapposite, and riddled with scope contradictions for regulating and imagining sex. We can do so much better than consent in our sexual politics. Fischel contends that sexual justice turns more productively on concepts of autonomy and access rather than consent. Cleverly humorous and adeptly researched, Screw Consent will have a significant impact on how we understand consent, sexuality, and law in the U.S. today"--Provided by publisher.